Inversion symmetry, architecture and dispersity, and their effects on thermodynamics in bulk and confined regions: From randomly branched polymers to linear chains, stars and dendrimers - Gujrati, P.D. (Condensed Matter Physics, 2002)
Theoretical evidence is presented in this review that architectural aspects can play an important role, not only in the bulk but also in confined geometries by using our recursive lattice theory, which is equally applicable to fixed architectures (regularly branched polymers, stars, dendrimers, brushes, linear chains, etc.) and variable architectures, i.e. randomly branched structures. Linear chains possess an inversion symmetry (IS) of a magnetic system (see text), whose presence or absence determines the bulk phase diagram. Fixed architectures possess the IS and yield a standard bulk phase diagram in which there exists a theta point at which two critical lines C and C′ meet and the second virial coefficient A₂ vanishes. The critical line C appears only for infinitely large polymers, and an order parameter is identified for this criticality. The critical line C′ exists for polymers of all sizes and represents phase separation criticality. Variable architectures, which do not possess the IS, give rise to a topologically different phase diagram with no theta point in general. In confined regions next to surfaces, it is not the IS but branching and monodispersity, which becomes important in the surface regions. We show that branching plays no important role for polydisperse systems, but become important for monodisperse systems. Stars and linear chains behave differently near a surface.